Low-Cost Embedded Hardware for RF Jamming Detection in IIoT Environments - Araújo, Patrícia R.; Faria, Décio R. M.; Bortoloto, Raul G. O.; Machado, Raphael C. S.; Gomes, Otávio S. M. (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg), 2026)
RF jamming attacks compromise the availability of wireless industrial systems regardless of the authentication and encryption state, representing a cyberattack vector capable of inducing operational failures that are difficult to detect. Existing approaches present limitations in complexity, cost, or integration that hinder their adoption in resource-constrained embedded systems. In this context, this work presents a low-cost embedded device for jamming detection, implemented for systems operating at 13.56 MHz or 433 MHz, with a focus on IIoT environments. The prototype was validated on a test bench with a maximum detection latency of 10.24 ms, enabling its use in environments with restricted operational budgets.